Molecular detection of Toxoplasma gondii in ready-to-eat salad mixes: multi-country survey using a validated and harmonised standard operating procedure, Europe, 2021 to 2022 - Calero-Bernal, Rafael; Betson, Martha; Slana, Iva; Bartosova, Barbora; Marucci, Gianluca; Possenti, Alessia; Álvarez-García, Gema; Bier, Nadja; Mayer-Scholl, Anne; Berg, Rebecca P; Chaudhry, Umer; López-Ureña, Nadia M; et al. (Euro surveillance, 2025)
BackgroundMost Toxoplasma gondii infections in humans are considered foodborne, but the relative importance of the various routes of infection is largely unknown. Consumption of green produce contaminated with T. gondii oocysts has been identified as a possible source.AimWe aimed to estimate the occurrence and prevalence of T. gondii oocysts in commercially available ready-to-eat (RTE) salad mixes in 10 European countries.MethodsA real-time PCR-based method for oocyst detection was developed and optimised by two laboratories and validated in an interlaboratory test. This detection method and a harmonised sampling strategy were applied in a multi-country study. Multivariable logistic regression was used to investigate risk factors for oocyst contamination of RTE salad.ResultsThe real-time PCR method had a detection limit of 10 oocysts per 30 g of salad. We collected 3,329 RTE salad samples (baby leaf and cut leaf mixes) from October 2021 to September 2022. The prevalence of T. gondii oocyst contamination was 4.1% (95% confidence interval (CI): 3.4-4.8%; n = 3,293). In multivariable regression analysis, winter season, sampling and packaging of salad in Northern Europe and production of salad in Western Europe were associated with detection of T. gondii, with no statistically significant differences between salad types.ConclusionWe estimated the prevalence of T. gondii oocysts in RTE leafy green salads using a validated and standardised procedure to assess the potential risk for human infection; highlighting the need to address this risk at each critical point of the salad production chain.
Keywords: harmonisation; Europe; Prevalence; Vegetables; Toxoplasmosis; Leafy greens; Food Contamination; zelenina; oocysts; oocysty; ring-trial; Oocysts; lidé; Evropa; Toxoplasma; prevalence; kontaminace potravin; potravinářská parazitologie; Toxoplasma gondii; Food Parasitology; ready-to-eat salads; toxoplazmóza; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans